Synthesis of a MnO2/Fe3O4/diatomite nanocomposite as an efficient heterogeneous Fenton-like catalyst for methylene blue degradation - Li, Zishun; Tang, Xuekun; Liu, Kun; Huang, Jing; Xu, Yueyang; Peng, Qian; Ao, Minlin (Beilstein Journal of Nanotechnology, 2018)
Heterogeneous Fenton-like catalysts with the activation of peroxymonosulfate (PMS), which offer the advantages of fast reaction rate, wide functional pH range and cost efficiency, have attracted great interest in wastewater treatment. In this study, a novel magnetic MnO2/Fe3O4/diatomite nanocomposite is synthesized and then used as heterogeneous Fenton-like catalyst to degrade the organic pollutant methylene blue (MB) with the activation of PMS. The characterization results show that the Fe3O4 nanoparticles and nanoflower-like MnO2 are evenly distributed layer-by-layer on the surface of diatomite, which can be readily magnetically separated from the solution. The as-prepared catalyst, compared with other Fenton-like catalysts, shows a superb MB degradation rate of nearly 100% in 45 min in the pH range of 4 to 8 and temperature range of 25 to 55 °C. Moreover, the nanocomposite shows a good mineralization rate of about 60% in 60 min and great recyclability with a recycle efficiency of 86.78% after five runs for MB. The probable mechanism of this catalytic system is also proposed as a synergistic effect between MnO2 and Fe3O4.
Keywords: diatomite; Fenton-like oxidation; hybrid catalyst; iron(II,III) oxide (Fe3O4); manganese(IV) oxide (MnO2)